Comparative Analysis of the Legal Status of an Unborn Child in Criminal Law in Nigeria, America, United Kingdom (UK), and India - Onuegbulam, Maria Chigozie (ABUAD Law Journal, 2021)
The Universal Declaration of Human Rights (UDHR) 1948 inspired all other human rights conventions and declarations adopted since after its proclamation by the United Nations General Assembly. Though most International and domestic Human Rights instruments lack a universal inclusion of the fetus as a person for the purposes of human rights, they provide for the protection of the same unborn child as a member of the human family. The American Convention on Human Rights for example guarantees the right to life and to the physical and mental integrity of the unborn child. Most countries have adopted it in providing legal measures for the protection of human fetus under the law. Progressively, Target-4 of the third Sustainable Development Goal (SDG 3.4) is positive on the point with an agenda of “leaving no one behind” and that of course includes the unborn child. Regrettably, some countries have consciously deviated from providing such protective laws for the rights of an unborn child. This research aims at analysing comparatively the legal status of an unborn child in criminal law in four common law countries. The objective is to highlight the need for both international and domestic recognition for the right of an unborn child. The study adopts doctrinal designs using comparative approaches with reliance on Statutes, case law, law reviews and data in web-based sources. The research found that except in America, the unborn child has no legal right. Consequently, there is need to guarantee the legal personality of the unborn child globally.